Selective Intraarterial Nimodipine Treatment in an Experimental Subarachnoid Hemorrhage Model - Firat, M. Murat (AJNR Am J Neuroradiol, 2005)
BACKROUND AND PURPOSE: Cerebral vasospasm secondary to subarachnoid hemorrhage (SAH) has been a serious clinical problem. The aim of the present study is to evaluate the efficacy of selective intraarterial (IA) nimodipine treatment in a rabbit model of chronic cerebral vasospasm. METHODS: Twenty-two adult New-Zealand rabbits of either sex, weighing 2500–3800 g were used for this study. Following a control angiography, all animals received 1 mL of fresh unheparinized autologuous arterial blood into the cisterna magna. Three days later, the presence of vasospasm was demonstrated angiographically by selective vertebral artery injection. The experimental design was as follows: separate groups of animals (n=5, in each group) received nimodipine (0.05 mg/kg), papaverine (6 mg/kg), or vehicle intraarterially, after placement of a microcatheter into the vertebral artery. Another group (n=5) received nimodipine (0.05 mg/kg) directly into the cisterna magna, and vehicle injection was made into cisterna magna in two other animals. Thirty minutes after treatment, angiographies were repeated and changes in arterial diameter were expressed as percentages of control. RESULTS: IA nimodipine and IA papaverine were effective in relieving veretebral and basilary vasospasm (P < .05). IA nimodipine was more effective than IA papaverine (P < .05). IA nimodipine was not more effective than intrathecal (IT) nimodipine in relieving vertebral artery vasospasm, although it was more effective than IT nimodipine in basilar artery. Vehicle injections (IA or IT) failed to reverse the vasospasm induced by autologuous blood injection. CONCLUSION: This study showed that selective IA nimodipine treatment may be considered as an alternative in the treatment of chronic vasospasm following SAH.